Characteristics of Chronic Sinusitis Based on Non-Contrast CT Scan at the ENT-Head and Neck Surgery Polyclinic of Regional General Hospital Dr. Zainoel Abidin Banda Aceh - Putra, Teuku Romi Imansyah; Teuku Husni T.R; Hesti Anandini Sariningrum; Dhiatama Endalif (Indonesian Journal of Tropical and Infectious Disease, 2022)
Chronic sinusitis is a long-term inï¬‚ ammation that occurs in the nasal and paranasal mucosa for 12 weeks. Non-contrast CT scan is gold standard in diagnosing chronic sinusitis. This study aims to determine the characteristics of chronic sinusitis based on non-contrast CT scan at the ENT-Head and Neck Surgery Polyclinic of RSUDZA Banda Aceh in 2019. This research was a descriptive study with retrospective data, medical record. The sample of this study was taken by consecutive sampling method in October 2020 and obtained 111 samples. The results showed that most patients with chronic sinusitis were 30-39 years), as many as 42 people (37.8%). Most of the sexes suï¬€ ering from chronic sinusitis were women, as many as 59 people (53.2%). Based on the non-contrast CT scan, the location of the sinuses most aï¬€ ected was the maxillary sinuses, as many as 110 people (99.1%). The number of sinuses that were most aï¬€ ected was single sinusitis, which was 58 people (52.3%). Most patients with chronic sinusitis without polyps were found, as many as 89 people (80.2%). The most common anatomical variation found was septal deviation as many as 25 people (22.5%). The conclusions in this study indicate that women, late adulthood, maxillary sinus, single sinusitis, chronic sinusitis without nasal polyps, and septal deviation are characteristics of chronic sinusitis patients based on non-contrast CT scan.